Drop impact printing - Modak, Chandantaru Dey; Kumar, Arvind; Tripathy, Abinash; Sen, Prosenjit (Nature communications, 2020)
Hydrodynamic collapse of a central air-cavity during the recoil phase of droplet impact on a superhydrophobic sieve leads to satellite-free generation of a single droplet through the sieve. Two modes of cavity formation and droplet ejection have been observed and explained. The volume of the generated droplet scales with the pore size. Based on this phenomenon, we propose a drop-on-demand printing technique. Despite significant advancements in inkjet technology, enhancement in mass-loading and particle-size have been limited due to clogging of the printhead nozzle. By replacing the nozzle with a sieve, we demonstrate printing of nanoparticle suspension with 71% mass-loading. Comparatively large particles of 20 μm diameter are dispensed in droplets of ~80 μm diameter. Printing is performed for surface tension as low as 32 mNm −1 and viscosity as high as 33 mPa∙s. In comparison to existing techniques, this way of printing is widely accessible as it is significantly simple and economical. Printing small droplets for a wide range of applications remains a challenge. Here, the authors propose a simple drop-on-demand printing technique which replaces the use of a nozzle with a sieve, enabling printing of nanoparticle suspension with 71% mass-loading, performed for surface tension range of 72–32 mNm-1 and viscosity up to 33 mPas.